Anatomic classification of mitral annular calcification for surgical and transcatheter mitral valve replacement. Issue 7 (2nd April 2021) - Alexis, Sophia L.; Alzahrani, Talal S.; Akkoc, Deniz; Salna, Michael; Khalique, Omar K.; El‐Eshmawi, Ahmed; Sengupta, Aditya; Hahn, Rebecca T.; Lerakis, Stamatios; Kini, Annapoorna; Sharma, Samin K.; Dangas, George D.; et al.
Abstract: Background and Aim of the Study: A systematic approach to quantify mitral annular calcification (MAC) in all‐comers by multidetector computed tomography (MDCT) is essential to guide treatment, but lacking. Methods: From September 2015 to July 2019, 82 patients with MAC underwent MDCT at two institutions to evaluate for surgical mitral valve replacement (SMVR), transcatheter mitral valve replacement (TMVR), or medical management. Type 1 MAC was defined as <270° annular calcium and Type 2 as ≥270°. Absence/presence of predicted left ventricular outflow tract (LVOT) obstruction with virtual valve placement was used to further define Type 2 MAC into 2A/B for our treatment algorithm. Results: Type 1 MAC was present in 51.2%, Type 2A in 18.3%, and Type 2B in 30.5%. Operable Type 1 patients (50.0%) underwent hybrid transatrial TMVR or SMVR. Type 2A underwent a variety of treatments, and Type 2B surgical candidates (40.0%) underwent hybrid transatrial TMVR secondary to difficult suture anchoring with significant MAC and predicted LVOT obstruction. At a follow‐up of 29.6 ± 12.0 months, mortality was 42.7% with 46.3% in the intervention group and 39.0% in the medical group ( p = 0.47). All percutaneous TMVR patients expired. This translated to a disproportionate number of Type 2A deaths (80.0% with intervention), but all were high/extreme surgical risk. The hybrid TMVR group consisted of 95.0% Type 1/2B patients and had a lower Society of Thoracic Surgeons predicted risk of operative mortality (7.4% vs. 9.2%, p = 0.43)/mortality. Conclusions: The highest mortality was seen in percutaneous TMVR Type 2A MAC patients, but they were at the greatest risk. Here we provide an objective MAC treatment algorithm for all‐comers based on operability/anatomy.